TAPHONOMIC ANALYSIS OF THE LATE EARLY PLEISTOCENE BONE REMAINS FROM BUIA (DANDIERO BASIN, DANAKIL DEPRESSION, ERITREA):EVIDENCE FOR LARGE MAMMAL AND REPTILE BUTCHERING (Rivista italiana di Paleontologia e Stratigrafia, 2004)
The Early Pleistocene sedimentary succession of the Dandiero (Buia) Basin (Danakil Depression, Eritrea) has preserved a rich paleontological, paleoanthropological, and archeological record circa one million years old. Fieldwork undertaken between 1995 and 2003 led to the collection of fossil vertebrate remains now stored at the National Museum of Eritrea. Bones were recovered in different localities of the Dandiero Basin, where abundant archaeological and paleontological remains outcrop from the eroded sediments. The faunal collection of 436 animal bones from the Buia Basin, mostly derived from Uadi Aalad area, have undergone taphonomic analysis. Even though bone surfaces are poorly preserved due to abrasion, our work demonstrates carcass exploitation. Some specimens, mostly representing Hippopotamus gorgops and medium- to large-sized bovids, show traces of butchering left by stone tools. We also document, as far as we know for the first time, a single case of butchering involving a femur of a crocodile.